The trajectory of archaic Greek trimeters - Kantzios, Ippokratis. (Mnemosyne, Supplements, 2005)
This volume makes clear that even within the short period of their floruit archaic Greek trimeters underwent profound changes. The shift in thematography, use of person, and vocabulary reveals that iambic verse is a complex, definable genre with all the dynamism that implies and with a traceable development. The various chapters examine the subject matter, morphology, and diction of the trimeters both within the genre in a diachronic fashion and in relation to elegy. The metrical inscriptions and later iambic poetry are also considered, as the author ponders the rise of tragedy and the disappearance of serious iambus. This work is of interest not only to scholars of archaic lyric poetry but also of tragedy and sympotic practices.